Personal electronic health records: Understanding user requirements and needs in chronic cancer care - Baudendistel, Ines; Winkler, Eva C.; Kamradt, Martina; Bernhard, Gerda; Eckrich, Felicitas; Heinze, Oliver; Bergh, Björn; Szecsenyi, Joachim; Ose, Dominik (JMIR medical education)
Background: The integration of new information and communication technologies (ICTs) is becoming increasingly important in reorganizing health care. Adapting ICTs as supportive tools to users' needs and daily practices is vital for adoption and use. Objective: In order to develop a Web-based personal electronic health record (PEPA), we explored user requirements and needs with regard to desired information and functions. Methods: A qualitative study across health care sectors and health professions was conducted in a regional health care setting in Germany. Overall, 10 semistructured focus groups were performed, collecting views of 3 prospective user groups: patients with colorectal cancer (n=12) and representatives from patient support groups (n=2), physicians (n=17), and non-medical HCPs (n=16). Data were audio- and videotaped, transcribed verbatim, and thematically analyzed using qualitative content analysis. Results: For both patients and HCPs, it was central to have a tool representing the chronology of illness and its care processes, for example, patients wanted to track their long-term laboratory findings (eg, tumor markers). Designing health information in a patient accessible way was highlighted as important. Users wanted to have general and tumor-specific health information available in a PEPA. Functions such as filtering information and adding information by patients (eg, on their well-being or electronic communication with HCPs via email) were discussed. Conclusions: In order to develop a patient/user centered tool that is tailored to user needs, it is essential to address their perspectives. A challenge for implementation will be how to design PEPA’s health data in a patient accessible way. Adequate patient support and technical advice for users have to be addressed. [J Med Internet Res 2015;17(5):e121]